“Ideias novas para problemas velhos" : a candidatura e campanha eleitoral de Leonel Brizola ao governo do Rio Grande do Sul em 1958 - Alves, Samuel da Silva (2020)
Over the last few years, the political performance of Leonel de Moura Brizola during the period of the brazilian democratic experience (1945-1964) has been the object of a lot of studies. However, most of these researches have dealt with Brizola's mandates, addressing in a partial way the elections in which he competed. Aiming to contribute to the studies about Brizola, the PTB and this period, this work deals with his performance as a candidate throughout this experience of democracy. Based on the theory of the political field developed by Pierre Bourdieu, we sought to analyze Brizola's candidacy and campaign to the government of Rio Grande do Sul in the 1958 elections. In this study, we sought to understand the Brizola's political rise inside your party and on the political scene of Rio Grande do Sul, as well as identifying the strategies of electoral mobilization and popularity building employed by Brizola in order to obtain victory in this election. At the same time, we also sought to understand what these questions reveal about the brazilian democratic experience, the PTB after 1954 and also about Brizola.